The Art of Forgetting - Izquierdo, Ivan (Springer International Publishing : Imprint: Springer, 2015)
How do we forget? Why do we need to forget? This book intends to answer to these and other questions. It aims to demonstrate that each one is who it is due to their own memories. Thus, distinguish between the information we should keep from those we should forget is an difficult art. In this book, the author discusses about the different types of memory, the main types of forgetting (avoidance, extinction and repression), their brain areas and their mechanisms. In this sense, the art of forgetting, or the art of do not saturate our memory mechanisms, is something innate, that benefits us anonymously, keeping us from sinking amidst our own memories. The essays that compose this book go through several aspects, since individuals to societies' memory. By the end of the book, the reader will be able to understand that we forget to be able to think, to live and to survive.